Cushing's Syndrome Pathophysiology, Diagnosis and Treatment - Bronstein, Marcello D. (Contemporary Endocrinology, 2011)
Cushing´s syndrome is a relatively rare clinical disorder that is associated with many co-morbidities such as systemic hypertension, diabetes, osteoporosis, impaired immune function and growth impairment in children, all of which severely reduce quality of life and life expectancy. Cushing's Syndrome: Pathophysiology, Diagnosis and Treatment reviews the difficulties in distinguishing Cushing's syndrome from these and other common conditions, such as central obesity, menstrual irregularity and depression. It also provides state-of-the-art information on various strategies to establish the diagnosis of Cushing's syndrome and the differential diagnosis among its diverse etiologies, as well as therapeutic approaches. Additionally, a range of conditions that represent challenges for the diagnosis and treatment--such as renal failure, pediatric age, cyclic hypercortisolism, and pregnancy--are covered in detail. A valuable resource not only for endocrinologists but also internal medicine physicians, gynecologists, pediatricians, , pituitary surgeons and urologists, Cushing's Syndrome: Pathophysiology, Diagnosis and Treatment provides insights by experts that will help all physicians dealing with Cushing´s syndrome to expand their knowledge about the condition and provide targeted, comprehensive care.